Dietary or enteral medium-chain triglyceride usage in a Chinese general hospital - Li, Rongrong; Ma, Jiangfeng; Yu, Kang; Wang, Lilin (Asia Pacific journal of clinical nutrition, 2015)
Objectives: Medium chain triglycerides (MCTs) are of nutritional interest for their unique properties on ingestion, absorption and metabolism. However, dietary and enteral MCTs usage in hospitalized patients in China requires evaluation. Methods: A retrospective analysis was conducted on 46 hospitalized patients who were administered MCTs therapy between January, 2012 and December, 2013 in Peking Union Medical College Hospital. The clinical parameters of subjects were evaluated 2 weeks after intervention. All indications and outcomes of MCTs therapy underwent evidence-based evaluation. A survey was conducted on a random sample of 77 doctors to clarify the awareness and knowledge of MCTs therapy among clinicians. Results: Among 46 cases undergoing MCTs therapy, there were 21 with gastrointestinal dysfunction (with improvement in 15 cases), 15 with lymphatic anomalies (with improvement in 7 cases), 5 with dyslipidemia (with improvement in 3 cases), 4 with exocrine pancreatic insufficiency (with improvement in 2 cases) and 1 with epilepsy (without improvement). All indications were evidence -based. Although MCTs were being utilized in an increasing number of patients, the survey revealed poor knowledge of their physicochemical properties, medical indications and the therapeutic basis of their use among clinicians. Conclusions: MCTs therapy is of benefit in the management of gastrointestinal malabsorption, pancreatic exocrine insufficiency, intestinal lymphangiectasia and dyslipidemia. However, randomized controlled trials with adequate sample size and longer follow-up are required to evaluate further their efficacy, and more educational programs are needed to ensure clinical competence for MCT therapy.